Two Modes of Riboflavin-Mediated Extracellular Electron Transfer in Geobacter uraniireducens - Huang, Lingyan; Tang, Jiahuan; Chen, Man; Liu, Xing; Zhou, Shungui (Frontiers in Microbiology, 2018)
Anaerobes respire extracellular electron acceptors by extracellular electron transfer (EET). It is widely recognized that flavins can act as electron shuttles to facilitate this process. Flavin synthesis genes are widely distributed in Geobacter species. However, the functions of flavins in the EET of Geobacter species are unclear. Here, we demonstrate that G. uraniireducens can secrete abundant riboflavin (up to 270 nM) to facilitate EET. When an electrode was used as the electron acceptor, the quick recovery of anodizing current after anolyte replacement and the electrochemical behavior of the G. uraniireducens biofilm characterized by differential pulse voltammetry suggest that the self-secreted riboflavin promoted EET by serving as bound redox cofactors for cytochromes. On the contrary, when Fe(III) oxide was the electron acceptor, free riboflavin acted as electron shuttle to mediate the reduction of Fe(III) oxide. The results demonstrate the flexibility of flavins in EET, suggesting that the properties of electron acceptors can affect the binding mode of extracellular flavins, and broaden the knowledge of the EET of Geobacter species.